Determination of Elastic Properties of Overburden Materials Using Intercept Time of Seismic Refraction in Ayede, South-Western Nigeria - Emmanuel Ikuemonisan, Femi; Olanrewaju Kayode, Yusuf; Segara Ajose, Anthony; Abiodun Okedeyi, Sakiru (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study investigates the elastic properties of overburden materials in Ayede, South-Western Nigeria, using the seismic refraction intercept time method. Seismic survey was conducted to obtain velocity profiles, which were then used to compute elastic parameters, including Young's modulus, shear modulus, and Poisson's ratio for the respective layers. The study reveals a stratigraphic progression from unsaturated sand at the surface to saturated tar sand, and finally to dense marl. The first layer, consisting of unsaturated sand, extends to a depth of 6.70 meters with a primary wave velocity (Vp) of 803 m/s, secondary wave velocity (Vs) of 305 m/s, and a density of 1650 kg/m³. The elastic properties include a bulk modulus of 0.859 x 10⁹ N/m² and a shear modulus of 0.154 x 10⁹ N/m². The second layer, comprising saturated tar sand, reaches a depth of 11.9 meters with a Vp of 1898 m/s, Vs of 737 m/s, and a density of 2045 kg/m³, yielding a bulk modulus of 5.886 x 10⁹ N/m² and a shear modulus of 1.111 x 10⁹ N/m². The final marl layer, the densest, exhibits a Vp of 3300 m/s, Vs of 1091 m/s, a bulk modulus of 21.55 x 10⁹ N/m², and a shear modulus of 2.796 x 10⁹ N/m².